The Role of the Regional Inspectorate in Supervising Village Financial Management - Siregar, Muhammad Syukur; Ritonga, Syafruddin; Jamaludin, Yanhar (Borong Newinera Publisher, 2025)
This study aims to analyze the performance of the supervision performance of the Regional Inspectorate of Mandailing Natal Regency on the financial management of Lumban Pasir Village in the 2022 and 2023 fiscal years. Supervision carried out by the Regional Inspectorate involves regular audits, monitoring, and evaluation of the planning, implementation, and reporting of the use of village funds. The research method used is qualitative with a descriptive approach, which includes in-depth interviews, observations, and document analysis. The results of the study show that although the Regional Inspectorate has carried out its supervisory function well, there are several obstacles that affect the effectiveness of supervision, such as limited human resources, lack of understanding of village officials about financial regulations, and lack of supporting facilities such as information technology. On the other hand, this supervision has succeeded in improving the quality of village financial planning and reporting, although there are still some weaknesses such as delays in financial reports and data inconsistencies. The impact of supervision on village financial management includes increasing awareness of the importance of transparency and accountability in the management of village funds. This study suggests the need to increase the capacity of village officials and Inspectorate auditors, as well as the use of information technology in the supervision process to improve the efficiency and effectiveness of village financial management.